2014
DOI: 10.1111/bjc.12065
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorder moderates outcome in short‐ and long‐term group analytic psychotherapy: A randomized clinical trial

Abstract: Clinical implications: LTG demonstrates better effectiveness than STG for patients with personality disorder co-morbidity (PD). Patients without PD do not appear to experience additional gain from attending LTG. Correct initial allocation to treatment duration may prevent disruptive breaks in relationships and lead to both human and economic cost savings. Limitations: Trials on mixed diagnostic samples may limit the ability to fully assess change for specific diagnostic groups. Therapists were unable to select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 56 publications
2
29
0
1
Order By: Relevance
“…Furthermore, patients with PD showed significantly greater improvement during the study period from 6 to 84 months with long-term compared to short-term therapy with regard to both symptomatic distress (between-group effect size, 0.6) and interpersonal problems (between-group effect size, 0.5). The between group effect sizes at 3-year follow-up, previously published (Lorentzen et al, 2015b), were 0.4 and 0.3 for GSI and mean IIP-C total, respectively. Thus, our 7-year follow-up demonstrated continuation and even further increase of this treatment effect, indicating a delayed effect of the long-term therapy compared to a sustained effect of the short-term therapy.…”
Section: The Moderator Effect Of Pd On Long-term Change In Symptoms Asupporting
confidence: 61%
See 3 more Smart Citations
“…Furthermore, patients with PD showed significantly greater improvement during the study period from 6 to 84 months with long-term compared to short-term therapy with regard to both symptomatic distress (between-group effect size, 0.6) and interpersonal problems (between-group effect size, 0.5). The between group effect sizes at 3-year follow-up, previously published (Lorentzen et al, 2015b), were 0.4 and 0.3 for GSI and mean IIP-C total, respectively. Thus, our 7-year follow-up demonstrated continuation and even further increase of this treatment effect, indicating a delayed effect of the long-term therapy compared to a sustained effect of the short-term therapy.…”
Section: The Moderator Effect Of Pd On Long-term Change In Symptoms Asupporting
confidence: 61%
“…During the first three years, we also found that patients with personality disorders (PDs) improved significantly more regarding symptoms, interpersonal problems, and psychosocial functioning in long-term than short-term therapy (Lorentzen, Ruud, Fjeldstad, & Høglend, 2015b). The moderating effect of presence of PD (indicated by number of positive SCID criteria) was only significant using GAF-S as an outcome measure, with an effect-size of 0.4.…”
Section: The Present Study 21 the Short-and Long-term Group Analyticmentioning
confidence: 88%
See 2 more Smart Citations
“…A review of PDtreatment recommended more structured groupbased treatment programmes for more severe PD and simpler, stand-alone formats of group psychotherapy for patients with milder personality problems (Verheul & Herbrink, 2007). However, significant improvements have been reported for PD-patients attending outpatient psychodynamic group psychotherapy (Jensen, Mortensen, & Lotz, 2010;Jorgensen et al, 2012;Lorentzen, Ruud, Fjeldstad, & Hoglend, 2014). Although the evidence-base is limited, these studies indicate a potential for treatment of PD in a stand-alone and outpatient group format.…”
Section: Introductionmentioning
confidence: 99%